All hallows - Golden, Christopher (St. Martin's Press, 2023)
"New York Times bestselling, Bram Stoker Award-winning author Christopher Golden is best known for his supernatural thrillers set in deadly, distant locales...but in this suburban Halloween drama, Golden brings the horror home. It's Halloween night, 1984, in Coventry, Massachusetts, and two families are unraveling. Up and down the street, secrets are being revealed, and all the while, mixed in with the trick-or-treaters of all ages, four children who do not belong are walking door to door, merging with the kids of Parmenter Road. Children in vintage costumes with faded, eerie makeup. They seem terrified, and beg the neighborhood kids to hide them away, to keep them safe from The Cunning Man. There's a small clearing in the woods now that was never there before, and a blackthorn tree that doesn't belong at all. These odd children claim that The Cunning Man is coming for them ... and they want the local kids to protect them. But with families falling apart and the neighborhood splintered by bitterness, who will save the children of Parmenter Road? All Hallows. The one night when everything is a mask ..."--